Penerapan Algoritma Block Cipher Odd-Even Confusing Key (OE-CK) Pada Aplikasi Pengamanan Video - Kartini, Dian Wahyuni; Ginting, Garuda; Ndururu, Eferoni (Bulletin of Data Science, 2023)
The problem that exists in the scope of the video is where the video that is privacy in nature can be watched by unauthorized people if the video file is without security. If there is a breach and theft of information on an important data in a video file, it will be detrimental to the interested parties. Therefore, an application system is needed to be able to secure the video file. To minimize this, a second level of security is needed, namely by scrambling the video so that visual information from the video cannot be seen by people without keys. Then the information in the video file is changed in the form of a code or signal where this code will be manipulated. Through the process of securing video files using the odd-even confusing key (OE-CK) block cipher algorithm, it is hoped that in the future this system can have a major effect on the security of video files from unauthorized breaches.